2015
DOI: 10.7314/apjcp.2015.16.2.565
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Cyrtopodion scabrum Extract on Growth of Human Breast and Colorectal Cancer Cells

Abstract: Breast and colorectal cancers rank high in Iran as causes of mortality. Most of the current treatments are expensive and non-specific. The potential anticancer properties of common home gecko, Cyrtopodion scabrum, were investigated in this study. The effects of C. scabrum extract on proliferation, viability and migration of the colorectal cancer (SW-742), breast cancer (MCF-7) and normal (MSC) cell lines were investigated using MTT and in vitro wound healing assay. IC 50 values calculated for the extract were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Extracts of Gekko japonicus showed antitumor effects against the human esophageal carcinoma EC9703 and mouse sarcoma S180 cell lines in experiments in vitro and in vivo [74]. Surprisingly, extracts derived from Cyrtopodion scabrum using ethanol and distilled water showed selective anticancer effects against the human breast cancer cell line MCF7 and human colon cancer cell line SW-742 through the inhibition of growth and migration, and they had no effect on normal mesenchymal stem cells [75]. In addition, the aqueous protein extracts of Eublepharis macularius induced apoptosis only in human cancer cell lines, such as bladder cancer 5637 and cervical cancer HeLa cells, via the inhibition of the PI3K/Akt signaling pathway, and without any effect on normal cells, including C2C12, NIH3T3, MEF, HEK293, Hs27 and NuFF cells [76,77].…”
Section: Extractsmentioning
confidence: 97%
“…Extracts of Gekko japonicus showed antitumor effects against the human esophageal carcinoma EC9703 and mouse sarcoma S180 cell lines in experiments in vitro and in vivo [74]. Surprisingly, extracts derived from Cyrtopodion scabrum using ethanol and distilled water showed selective anticancer effects against the human breast cancer cell line MCF7 and human colon cancer cell line SW-742 through the inhibition of growth and migration, and they had no effect on normal mesenchymal stem cells [75]. In addition, the aqueous protein extracts of Eublepharis macularius induced apoptosis only in human cancer cell lines, such as bladder cancer 5637 and cervical cancer HeLa cells, via the inhibition of the PI3K/Akt signaling pathway, and without any effect on normal cells, including C2C12, NIH3T3, MEF, HEK293, Hs27 and NuFF cells [76,77].…”
Section: Extractsmentioning
confidence: 97%
“…scabrum was provided by the Razi Research Institute of Vaccine & Serum, Shiraz, Iran, and was identified and approved by a taxonomist (F.Torki, the head of the department at FTEHCR). The aqueous C. scabrum Whole Extract (CWE) was obtained as described previously by Amiri et al with minor modifications (Amiri et al, 2015). In brief, all animals were cleaned, ground, and homogenized by a homogenizer (Bodine Electric Company, Chicago, USA).…”
Section: Preparation Of Aqueous Extract From Cyrtopodion Scabrummentioning
confidence: 99%
“…(Rastegar-Pouyani et al, 2010). Recently, we have reported the antiproliferative effects of its extract on the human breast, colorectal, stomach, and liver cancer cells, with the highest inhibitory effect on the colorectal cancer cells without any significant harmful effect on the normal cells (Amiri et al, 2015;Rashidi et al, 2017). By obtaining the evidence from in-vivo studies, using colorectal tumor-bearing mice, we also have demonstrated that C. scabrum extract (CCE) significantly decreased the mean scores of tumor weight and volume as well as 5-fluorouracil (5-FU) chemotherapy drug, while interestingly, unlike 5-FU, hemato-immunological indices and liver function were maintained as normal; also, the treated mice demonstrated good physical activity and normal weight gain (Babaei et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The whole animals were ground to a fine powder and further extracted (water extraction and ethanol precipitation) to obtain Gecko Sulphated-Polysaccharide-Polypeptide (GSPP), which were then desalted, dialyzed and freeze dried for later use. The procedure was carried out exactly according to the protocol described previously (20,23,26).…”
Section: Preparation Of Aqueous Extract From Animalsmentioning
confidence: 99%
“…According to traditional Chinese medicine (TCM), several studies have shown that the whole body of a kind of lizard, named Gecko Swinhonis Guenther, has been used to treat various diseases such as cancer for decades (19)(20)(21)(22). Recently, we have reported the inhibitory effect of Cyrtopodion scabrum (so called roughtailed home gecko) extract on the human breast and colorectal cancer cells (23). The rough-tailed geckonid lizards have 15 -16 species distributed in southwestern, central and eastern parts of Iran (24,25).…”
Section: Introductionmentioning
confidence: 99%